The effect of deformation-induced-ferrite-transformation on nanometre-sized carbides in Ti–Mo ferritic steel. Issue 10 (3rd July 2017) - Ning, Zhen; Cai, Qingwu; Xie, Baosheng; Dong, Entao
ABSTRACT: In this study, the effect of deformation-induced-ferrite-transformation (DIFT) rolling on precipitation in Ti–Mo ferrite matrix micro-alloyed steel was investigated by comparing to rolling in austenite non-recrystallisation region. The precipitate volume fraction and precipitation-starting time-temperature (PTT) curves under two kinds of process were calculated by thermodynamic and kinetic calculation, and the effects of non-recrystallisation rolling and DIFT rolling on the contribution of strengthening mechanisms were quantitatively analysed. The results showed that comparing with rolling in the austenite non-recrystallisation region, carbides in the steel by DIFT rolling were finer and more uniform. Moreover, DIFT rolling could enhance fine grain strengthening and precipitation strengthening simultaneously, and the increments of fine grain and precipitation strengthening were 34 and 63.7 MPa, respectively.